Bioactive compounds and medicinal properties of fruit juices. (12th September 2014) - Bhardwaj, Raju Lal; Nandal, Urvashi; Pal, Ajay; Jain, Shashi
Abstract : The product . Fruit juices have attained an important place in the modern diets of people belonging to different communities and classes world over. It is the unfermented but fermentable liquid obtained from the edible part of sound, appropriately mature and fresh fruit.Bioactive compounds . Fruit juices contain nutrients like vitamins, minerals, trace elements, energy and phytochemicals including flavonoids, polyphenols and antioxidants that have been shown to have varied health benefits.Medicinal properties . The mode of action of these fruit juice compounds in most cases seems to be by modulating gene activities. Fruit juice as part of a balanced diet offers both good health and profound disease risk reduction properties. As a result, there is high demand as alternative medicine for different kinds of illnesses such as chronic inflammation, arthritis, diabetes, high blood pressure, muscle aches and pains, menstrual difficulties, headaches, heart disease, AIDS, cancers, gastric ulcers, sprains, mental depression, poor digestion, arteriosclerosis, blood vessel problems, and drug addiction. Furthermore, to identify fruit juices as non-consumable in the context of obesity and dental health would deprive the consumer of a perfectly healthy and nutritious food, and would be completely contrary to the evidence noted in the scientific community.Discussion and conclusion . Fruit juices are an excellent choice of drink when consumed moderately as per recommendations.